Thioflavin t behavior in lysozyme - lipid systems - Gorbenko, G. P.; Ioffe, V. M.; Kinnunen, P. K.J. (Biophysical Bulletin, 2005)
The applicability of thioflavin T (ThT) to the detection of amyloid-like aggregates formed in the membrane environment was evaluated using a lysozyme-lipid model system. It was found that ThT is capable of partitioning into lipid bilayers composed of zwitterionic (1- palmitoyl -2-oleoyl-sn-glycerol-3-phosphocholine (POPC)) and anionic (1-palmitoyl-2-oleoyl-sn-glycerol-3-phosphoglycerol (POPG)) phospholipids. The ability of ThT to associate non-specifically with lysozyme in its native state was uncovered. These properties of ThT may impose limits on the use of this dye for the identification of membrane-induced fibrillar structures.